2019
DOI: 10.1001/jamaophthalmol.2019.2433
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Disease Progression With a Quantitative Severity Scale for Retinopathy of Prematurity Using Deep Learning

Abstract: ; for the Imaging and Informatics in Retinopathy of Prematurity Consortium IMPORTANCE Retinopathy of prematurity (ROP) is a leading cause of childhood blindness worldwide, but clinical diagnosis is subjective and qualitative. OBJECTIVE To describe a quantitative ROP severity score derived using a deep learning algorithm designed to evaluate plus disease and to assess its utility for objectively monitoring ROP progression. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study included images from 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 33 publications
1
72
0
Order By: Relevance
“…Although the number of pre-plus images available for evaluation was relatively small, this may support reports that plus disease likely exists as a continuous spectrum of retinal vascular abnormality (Fig. 4),29,36 a hypothesis also suggested in recent ROP deep learning literature 29,37,38. With significant further development and validation, the algorithm may be able to assist in the objective quantification of ROP disease severity and the monitoring of disease progression.…”
Section: Discussionsupporting
confidence: 72%
“…Although the number of pre-plus images available for evaluation was relatively small, this may support reports that plus disease likely exists as a continuous spectrum of retinal vascular abnormality (Fig. 4),29,36 a hypothesis also suggested in recent ROP deep learning literature 29,37,38. With significant further development and validation, the algorithm may be able to assist in the objective quantification of ROP disease severity and the monitoring of disease progression.…”
Section: Discussionsupporting
confidence: 72%
“…Redd et al reported that a scale from 1 to 9 could accurately detect type 1 ROP with an area under the curve of 0.95 and, in theory, could decrease the number of ophthalmoscopic examinations by 80% in a real-world telemedicine program because most babies will have no or mild disease. 34 More recently, Taylor et al 35 implemented the i-ROP DL algorithm to assign a continuous ROP vascular severity score (1)(2)(3)(4)(5)(6)(7)(8)(9) and to classify images based on severity: no ROP, mild ROP, type 2 ROP, and preplus disease, or type 1 ROP. Using reference standard diagnoses, this retrospective cohort study concluded that the continuous ROP vascular score was associated both with the ICROP category of disease at a single point in time, and clinical progression of ROP over time.…”
Section: A Continuous Severity Score For Ropmentioning
confidence: 99%
“…Using reference standard diagnoses, this retrospective cohort study concluded that the continuous ROP vascular score was associated both with the ICROP category of disease at a single point in time, and clinical progression of ROP over time. 35 Gupta et al 36 showed that these continuous scores reflected posttreatment regression in eyes with treatment requiring-ROP. Using i-ROP data, this group also found that eyes requiring multiple treatment sessions (laser or intravitreal injection of bevacizumab) had higher pretreatment ROP vascular severity scores compared with eyes requiring only a single treatment, suggesting that treatment failure may be related to more aggressive disease or disease treated at a later stage.…”
Section: A Continuous Severity Score For Ropmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of disease severity and change over time on medical images are important and routine tasks. For example, vascular changes in retinopathy of prematurity (ROP) can be an important biomarker of disease progression and response to therapy 1,2 . For many types of pathologies, the disease process can have a wide continuous spectrum of severities, which can change over time.…”
Section: Introductionmentioning
confidence: 99%